Use of multidisciplinary investigation for the diagnosis of urban linear processes in a voçoroca in the Bequimão Neighborhood - São Luís - MA - Oliveira, Felipe Ferreira (2020)
Linear erosive processes have been effective modifiers of the urban landscape of the island of São Luís, in a phenomenon that is fruit of the accelerated erosion caused by the anthropic action. Due to its complexity, the study of this phenomenon requires a multidisciplinary investigation. The objective of this work is to vewrify the efficiency of a proposal of multidisciplinary diagnosis of the susceptibility to erosion of an area. For that, a gully located in the Bequimão neighborhood, in São Luís (MA), was used as reference area. In addition, it is also sought to collaborate to better understand the genesis and evolution of an erosive process in gully stage. The methodology adopted in this work consists of the multidisciplinary study of the erosive process considering the following aspects: geotechnical characterization, characterization of the physical environment, soil use and vegetation cover. The results of the research indicate that all the erosive conditioning factors considered in this work collaborate for the evolution of the phenomenon, confirming that the parameters selected for the multidisciplinary analysis are good indicative of the process and, when taken together, allow identifying with good reliability areas susceptible to erosion.